(64x-3x+19)=

Simple and best practice solution for (64x-3x+19)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (64x-3x+19)= equation:


Simplifying
(64x + -3x + 19) = 0

Reorder the terms:
(19 + 64x + -3x) = 0

Combine like terms: 64x + -3x = 61x
(19 + 61x) = 0

Remove parenthesis around (19 + 61x)
19 + 61x = 0

Solving
19 + 61x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + 61x = 0 + -19

Combine like terms: 19 + -19 = 0
0 + 61x = 0 + -19
61x = 0 + -19

Combine like terms: 0 + -19 = -19
61x = -19

Divide each side by '61'.
x = -0.3114754098

Simplifying
x = -0.3114754098

See similar equations:

| -8(1-8v)=-520 | | 4x+1-8=-19 | | -8(1-8v)=-530 | | 6(c+5)=-36 | | 7m-3m=16 | | 3x+3(2x+11)=132 | | 9=b-2 | | 2.6=9.3/x | | 12=3+4b+5 | | 7/2-2/3= | | 9=xb-2 | | 5n+8(4n-3)=161 | | 137=7(3x+7)+x | | x^4+x^9=6 | | -14.2=-1.5k+3.2 | | x-4=10+8 | | -4.8p+2.2=17.56 | | 0.60x-1.05(150)=0.30(93) | | 6[3b-2]+5b=57 | | 27-11x=-3 | | -2y-22=5y+13 | | 7=×/5-1 | | 4[3x+2]=56 | | 7(5x+8)=(x-4) | | n/15-1=0 | | -7.3+x=8.7 | | 101.55-X=42.86 | | 4(2y+5)=5-3(y-5) | | 13-x=391 | | -7y-12=3y+8 | | -310=5n+7(-7n+6) 13 | | 5+[2x-1]=8 |

Equations solver categories